The collateral damage of the COVID-19 pandemic on homeless people in the Netherlands; a qualitative study on the impact of health and care - van Loenen, Tessa; Sow, Jeyna; van den Muijsenbergh, Maria (Frontiers in Medicine, 2024)
People experiencing homelessness, also in the Netherlands, experience poorer physical and mental health compared to the general population and suffer from unmet health needs that are strongly related to their unfavorable social situation. This makes them especially vulnerable to negative consequences of a public health emergency such as the COVID-19 pandemic. This qualitative study aims to provide insight into the experiences of people experiencing homelessness with the impact of the pandemic on their health and lives.We performed semistructured interviews at 3 different times in the first two years of the pandemic including respectively 67, 55 and 53 persons. Interviews focused on their experienced mental and physical health, their experiences with the public health measures taken, and the care they received during the pandemic.In each round of interviews, the self-reported mental health was lower than before. In the last round approximately half felt mentally unhealthy. Mental health was negatively impacted due to livelihood insecurity, loss of social contact and poor accessibility to social and medical care. Twenty-four hour shelter locations with smaller dormitories had a positive impact on mental health.Most preventive measures taken during the pandemic negatively impacted the mental health of people experiencing homelessness but some improved their health. We recommend special attention to the effects on mental health when planning measures for pandemic control and we recommend to implement 24-hour shelter and smaller dormitories. Some global studies have illustrated how the pandemic has affected this population, encompassing health, social, and economic dimensions (14-17). A study in the Netherlands showed that the actual COVID-19 infection among individuals experiencing homelessness was less than previously anticipated, and contradictory to some other countries (12,(18)(19)(20)(21). Limited information exists about how these people have coped with PHSM and pandemic-related life disruptions.This study aims to shed light on the experiences of persons experiencing homelessness in the Netherlands during the pandemic and the effects they experienced on their mental well-being and lives. Understanding these factors can offer valuable insights for molding future pandemic responses